The Effect of “Friends” Program Training on the Loneliness of 8-18 Years Old Children with Thalassemia Major in Golestan Province of Iran - Masoumeh Ghorbanpour; Farhad Aref; Atefeh Haghparast; Haniye Asadinejad; Gol Bahar Akhondzadeh (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction: Beta thalassemia is an inherited genetic disorder that is associated with severe physical and mental illnesses. The aim of this study was to investigate the effect of “Friends” program training on the loneliness of children with thalassemia major at thalassemia centers of Golestan.Materials and Methods: This quasi-intervention study with two intervention and control groups was conducted on 50 children with thalassemia major aged 8-18 years referred to thalassemia centers in Golestan province in 2019. In the intervention group, the Friends program training was carried out in ten 60-minute long sessions. Demographic information form and Asher’s children loneliness questionnaire were the tools used for data collection. The collected data were analyzed using SPSS software version 25 at the significance level of P < 0.05.Results: The results showed that, the mean score of loneliness before the intervention was 33.32 ± 10.61 in the intervention group and 41.4 ± 12.20 in the control group. The mean score of loneliness after the intervention decreased to 28.36 ± 7.74 in the intervention group, and 40.68 ± 11.68 in the control group. The ANCOVA test showed a significant difference in the mean score of loneliness after the intervention by removing the effect of pretest (P = 0.01). Conclusion: The use of Friends program training can be considered as an efficient method in improving medical outcomes related to the loneliness of children with thalassemia and limiting unnecessary health care costs.